RNA-seq and Analysis of Argyrosomus japonicus Under Different Salinities - Zhujun Li (Frontiers Media S.A., 2021)
Salinity variation affects the physiological processes of fish. This study analyzed the transcriptome of the gill tissue of Argyrosomus japonicus to determine the significantly differentially expressed genes (DEGs) of A. japonicus under salinity changes. Transcriptome analysis of nine samples yielded 55.873 Gb of clean data, 64,912 transcripts, and 29,567 unigenes, and 83.62% of the transcripts and 81.89% of the unigenes were annotated. Compared with the control group, the high- and low-salt groups showed 1,731 and 695 DEGs, respectively. Gene Ontology enrichment analysis revealed that the DEGs were significantly enriched in transportation, metabolism, and stress response. Kyoto Encyclopedia of Genes and Genomes pathway enrichment revealed that the DEGs were significantly enriched in some signaling pathways. Several key genes (KRT1, KRT2, ATP1A, LDH, PFN, ACTB_G1, TUBB, GZMB, MHC2, CCL19, EPX, ANXA5, ACBP, EHF, BHMT, COL1A, and RHOA) were related to salinity adaptation. When environmental salinity fluctuated, genes related to stress, immunity, ion transport, and metabolism became more sensitive. These results suggest that the adaptation of A. japonicus under salinity changes is a complex process that involves multiple genes acting together.